The bioarchaeology of cardiovascular disease - Binder, Michaela 1982-; Roberts, Charlotte A. 1957-; Antoine, Daniel (Cambridge studies in biological and evolutionary anthropology, 2023)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide today, but are not just a modern phenomenon. To explore the deep roots of CVDs in human history, this book brings together bioarchaeological evidence from different periods, as old as 5000 BC, and geographic locations from Alaska to Northern Africa. Experts in their fields showcase the powerful tool set available to bioarchaeology, which allows a more comprehensive reconstruction of the human past through evidence for disease. The tools include aDNA and histological analyses and digital imaging techniques for studying skeletal and mummified human remains